Testing for Asymmetric Employer Learning - Schönberg, Uta (Journal of Labor Economics, 2007)
Recent evidence suggests that employers acquire more precise information about a worker’s productivity the more time he or she spends in the labor market. The following question arises: Is learning symmetric, that is, do all employers have the same information about workers’ productivity, or is learning asymmetric, that is, does the current employer have superior information about workers’ productivity? This article develops a learning model with endogenous mobility that nests both learning hypotheses. It then proposes new tests for asymmetric employer learning. Overall, learning appears to be mostly symmetric, except possibly when the employees involved are college graduates.